Labelisasi Pengurus Ranting NU dalam Peningkatan Ghirah Berkhidmat dan Membentengi dari Faham Radikalisme Desa Bekiring Ponorogo - Shodiq, Ja'far; Susanto, Hanafi Hadi (Social Science Academic, 2025)
This work and research program aims to reduce the influx of radicalism in Bekiring Village through dedication in the form of labeling/plangisation of Bekiring Village NU branch and committee members and also labeling of assets in the form of mosques, prayer rooms and also educational institutions such as Al-Quran Education Parks (TPQ) and so on. The method used in this study is ABCD (Asset Based Community Driven-Development) in the form of installing signs at the houses of the NU branch management and NU banom. The results of this study are that the impact of the work program is starting to be seen, namely an increase in enthusiasm to serve the NU Branch Managers of Bekiring Village to the NU organization, this was evidenced during the Clean village grand recitation on Monday evening Tuesday, August 7 2023 which was filled in by K.H.Ja'far Shidiq Al Badawi caretaker of the Sendang Drajad Jambon Islamic Boarding School, Ponorogo, all the administrators of the NU Branch and the NU Banoms worked together hand in hand to make the event a success, where previously there were gaps and miss communication between administrators now there has been good communication well, and also to prevent/protect radicalism from entering Bekiring Village, because they will think that their ideology has no room anymore in Bekiring Village, Pulung District, Ponorogo Regency.